Study of Tanqih al-Qaul al-Hatsits: The Book of Sheikh Nawawi al-Bantani - Muhammad Nurzakka (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
Using the descriptive-analytical method, this paper discusses the role of Sheikh Nawawi al-Bantani in the development of hadith studies in Indonesia through his book called Tanqih al-Qaul al-Hasis which is a syarh (review) of the Lubab al-Hadis by Imam Suyuti. In general, Sheikh Nawawi used the ijmali method in writing the book and sometimes also used the tahlili method. The characteristics of the book include: Sheikh Nawawi mentions verses of the Qur'an that have a correlation with the theme of the chapter, there are part of the book describing the biographies of the Prophet’s companions, there are some explanations about the meaning of hadith which includes interpretation, hadith values, and comments on the quality of hadith, Syekh Nawawi uses sufistic approach in explaining hadith, sometime Syekh Nawawi describe the content of hadith using the fiqh perspective.